How does Congress approach population and family planning issues? : results of qualitative interviews with legislative directors - Patterson, Sally (Rand, 1999)
Congressional opinions on issues related to population are highly polarized. Approximately 90 percent of Congress consistently votes either uniformly to support or uniformly to oppose population-related legislation--so the remaining 10 percent is likely to determine the fate of such initiatives. To determine how this critical group makes its decisions, researchers interviewed a sample of legislative directors (chosen as proxies, to allow in-depth interviews). Most respondents felt that the United States should continue to play a leading role internationally, but several also stressed that their members of Congress favor increased emphasis on multilateral approaches. A majority felt that world population growth is a problem but is not urgent. Nearly unanimous support was expressed for U.S. support of voluntary family planning when it is understood to exclude abortion. Congress would benefit from research-based, factual information on a variety of international population issues.